2017
DOI: 10.1159/000460819
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma Outcome: A Retrospective Study from 3 Tertiary Centers in Saudi Arabia

Abstract: Background: Hodgkin lymphoma (HL) exhibits considerable clinicopathological variations in different parts of the world. This study was prompted by the limited availability of HL data in developing countries (particularly long-term outcomes). Methods: We performed a retrospective review of eligible adult HL patients treated at 3 tertiary centers in Saudi Arabia between January 1997 and December 2012. Results: The review included 340 patients with a median age of 26 years (range 15-82 years); 53% were male, 74% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
8
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
5
8
0
6
Order By: Relevance
“…Malignant lymphoma was predominantly perceived in males compared to females. Studies from Saudi Arabia and other countries have shown similar findings [16] [17]. In this study, approximately 83.3% of the cases of HL were males, which is very high percentage compared to other reports [16].…”
Section: Discussionsupporting
confidence: 83%
“…Malignant lymphoma was predominantly perceived in males compared to females. Studies from Saudi Arabia and other countries have shown similar findings [16] [17]. In this study, approximately 83.3% of the cases of HL were males, which is very high percentage compared to other reports [16].…”
Section: Discussionsupporting
confidence: 83%
“…However, it may recur after the age of 50 years. In one study from Saudi Arabia, the overall survival rate of patients with HL was found to be 91% [59] . Recent studies showed that infection with hepatitis C&B viruses is a common risk factor [60] .…”
Section: Resultsmentioning
confidence: 99%
“…The OR (95%CI) ranged from 1.0 (0.60–1.80) to 5.5 (3.97–7.92). Two studies have assigned genetic and Epstein-Barr viral infection as a possible risk factor for Hodgkin and non-Hodgkin lymphoma, OR (95%CI) 5.5 (3.9–8.0) and 5.8 (4.9–7.0) [19] , [59] . A high degree of heterogeneity was observed in the present analysis (I 2 = 92.6%; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies from Europe have reported similar figures [ 7 , 32 ]. In contrary, at least more than half of HL patients in developing countries are diagnosed with advanced stage disease [ 9 , 10 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%